2017
DOI: 10.1371/journal.pone.0178251
|View full text |Cite|
|
Sign up to set email alerts
|

The learning curve of endoscopic total mastectomy in Taiwan: A multi-center study

Abstract: IntroductionLaparoscopic techniques are commonly used in abdominal and gynecologic surgery, while breast cancer surgery has remained largely unchanged. In Asia, especially in Japan, many surgeons have started to use endoscopic surgery for breast cancer. In Taiwan, endoscopy-assisted breast surgery started in 2010. The benefits of this surgical method include smaller incisions, an axillary anatomic approach, clear vision, no oncologic compromise, and good cosmetic outcomes. This is the first report to discuss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Despite a thorough preparation through previous studies on E-NSM, it took time to adapt to the new surgical view, endoscopic device, and position of the endoscope. The study by Hung et al [ 19 ] on the learning curve of endoscopic total mastectomies showed that the inflection point occurred after 15 to 17 cases. In our cases, the operative time for NSM decreased sharply after approximately 10 cases ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a thorough preparation through previous studies on E-NSM, it took time to adapt to the new surgical view, endoscopic device, and position of the endoscope. The study by Hung et al [ 19 ] on the learning curve of endoscopic total mastectomies showed that the inflection point occurred after 15 to 17 cases. In our cases, the operative time for NSM decreased sharply after approximately 10 cases ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Operation time and hospital stay are relevant parameters for the outcome of microsurgical free flaps in the literature. 17,[26][27][28] Inpatient stays and operation times were significantly reduced in cohort B (►Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…However, high-level evidence of endoscopic surgery for breast cancer treatment is still lacking [38]. All patients exhibited no significant difference in postoperative survival, local recurrence or distant metastasis, and postoperative complications compared with open surgery [40][41][42][43]. And the patients receiving minimally invasive surgery is also higher than those receiving open surgery [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%